2018
DOI: 10.1111/bph.14331
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the effects of the endocannabinoid system in cancer: a review

Abstract: In the last few decades, the endocannabinoid system has attracted a great deal of interest in terms of its applications to clinical medicine. In particular, its applications in cancer probably represent one of the therapeutic areas with most promise. On the one hand, expression of the endocannabinoid system is altered in numerous types of tumours, compared to healthy tissue, and this aberrant expression has been related to cancer prognosis and disease outcome, suggesting a role of this system in tumour growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 128 publications
1
78
0
6
Order By: Relevance
“…Despite the reported evidence, the altered expression of CB receptors in several GI cancers is not strictly related to a straightforward cause and effect and must be further investigated. However, cannabinoids' action in GI cancers has been demonstrated in vitro and in vivo, indicating their antiproliferative, proapoptotic, and antimetastatic properties [41]. Of note, it has been demonstrated that endogenous cannabinoid agonists, such as AEA (0.5-5 µM) and its metabolic-stable analogous, Meth-AEA (0.5-5 µM), diminished the volume and the density of gastric carcinomas cells, inducing apoptosis and necrosis, respectively [42].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…Despite the reported evidence, the altered expression of CB receptors in several GI cancers is not strictly related to a straightforward cause and effect and must be further investigated. However, cannabinoids' action in GI cancers has been demonstrated in vitro and in vivo, indicating their antiproliferative, proapoptotic, and antimetastatic properties [41]. Of note, it has been demonstrated that endogenous cannabinoid agonists, such as AEA (0.5-5 µM) and its metabolic-stable analogous, Meth-AEA (0.5-5 µM), diminished the volume and the density of gastric carcinomas cells, inducing apoptosis and necrosis, respectively [42].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…In addition, the heterogeneity of endocannabinoids and their receptors in different tumor types raises the possibility that specific cannabinoid compositions should be used to treat differing cancer subtypes. 3,9,10…”
Section: Cannabis and Cancermentioning
confidence: 99%
“…Since its initial discovery, the endocannabinoid system has been studied for its potential involvement in a wide range of pathophysiological processes linked to conditions such as cancer (Fraguas‐Sánchez et al . ), inflammatory bowel diseases (Leinwand et al . ), type 2 diabetes (Gruden et al .…”
Section: Pharmacology Of Cbdmentioning
confidence: 99%